Risk factors for anastomotic leakage and leak‐related mortality after colonic cancer surgery in a nationwide audit. Issue 4 (March 2014) - Bakker, I. S.; Grossmann, I.; Henneman, D.; Havenga, K.; Wiggers, T.
<x xml:space="preserve">Abstract</x> Background Surgical resection with restoration of bowel continuity is the cornerstone of treatment for patients with colonic cancer. The aim of this study was to identify risk factors for anastomotic leakage (AL) and subsequent death after colonic cancer surgery. Methods Data were retrieved from the Dutch Surgical Colorectal Audit. Patients undergoing colonic cancer resection with creation of an anastomosis between January 2009 to December 2011 were included. Outcomes were AL requiring reintervention and postoperative mortality following AL. Results AL occurred in 7·5 per cent of 15 667 patients. Multivariable analyses identified male sex, high American Society of Anesthesiologists (ASA) fitness grade, extensive tumour resection, emergency surgery, and surgical resection types such as transverse resection, left colectomy and subtotal colectomy as independent risk factors for AL. A defunctioning stoma was created in a small group of patients, leading to a lower risk of leakage. The mortality rate was 4·1 per cent overall, and was significantly higher in patients with AL than in those without leakage (16·4 versus 3·1 per cent; P < 0·001). Multivariable analyses identified older age, high ASA grade, high Charlson score and emergency surgery as independent risk factors for death after AL. The adjusted risk of death after AL was twice as high following right compared with left colectomy. Conclusion The elderly and patients with co‐morbidity have a higher risk of death after AL. Accurate preoperative patient selection, intensive postoperative surveillance for AL, and early and aggressive treatment of suspected leakage is important, especially in patients undergoing right colectomy.